Nuremberg [videorecording (DVD)] : les Nazis face à leurs crimes = Nuremberg : the Nazis facing their crimes - Delage, Christian; Gaston-Dreyfus, Gilles; Plummer, Christopher (Arte France ; Imavision [distributor], 2006)
"Nuremberg, November 20, 1945--The trials of Nazi war criminals begins in a city still in ruins, barely six months after the Germans' surrender. The United States, France, Great Britain and the USSR unite to deliver exemplary justice in response to crimes against peace and, for the first time in history, to "crimes against humanity". On the accused bench sit 21 of the highest Nazi dignitaries, including Hermann Göring, Rudolph Hess, Joachim von Ribbentrop and Wilhelm Keitel. They all plead not guilty, although the "atrocities" committed are tremendous. As evidence, films of the liberation of the concentration camps would be screened, an unprecedented move, during the proceedings. Evidence is presented, confrontations arise, testimonies of executioners and victims are heard. After 10 months of hearings, the verdict is rendered: 12 defendants sentenced to death penalties, including one in absentia, seven sentenced to prison and three acquitted. Thus ends the trial that paved the way for the creation of international tribunals."--Container.